2018
DOI: 10.1007/jhep02(2018)151
|View full text |Cite
|
Sign up to set email alerts
|

Complex Langevin analysis of the spontaneous symmetry breaking in dimensionally reduced super Yang-Mills models

Abstract: In recent years the complex Langevin method (CLM) has proven a powerful method in studying statistical systems which suffer from the sign problem. Here we show that it can also be applied to an important problem concerning why we live in fourdimensional spacetime. Our target system is the type IIB matrix model, which is conjectured to be a nonperturbative definition of type IIB superstring theory in ten dimensions. The fermion determinant of the model becomes complex upon Euclideanization, which causes a sever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 76 publications
(152 reference statements)
7
44
0
Order By: Relevance
“…As a promising approach to overcome this problem, we may use the complex Langevin method [38,39], which has attracted much attention recently [40][41][42][43][44][45][46]. It was successful also in investigating the SSB of rotational symmetry in the 6d Euclidean type IIB matrix model [7]. Preliminary results [31] for the bosonic Lorentzian model suggest that by approaching θ = π/2, one obtains clear deviations from the Pauli-matrix structure without losing the (3+1)d expanding behavior.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising approach to overcome this problem, we may use the complex Langevin method [38,39], which has attracted much attention recently [40][41][42][43][44][45][46]. It was successful also in investigating the SSB of rotational symmetry in the 6d Euclidean type IIB matrix model [7]. Preliminary results [31] for the bosonic Lorentzian model suggest that by approaching θ = π/2, one obtains clear deviations from the Pauli-matrix structure without losing the (3+1)d expanding behavior.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The model, therefore, has the potential to clarify a possible nonperturbative mechanism for dynamical compactification in superstring theory. The Euclidean version of the model was investigated from this viewpoint, and the spontaneous breaking of SO(10) rotational symmetry was suggested by various approaches [2][3][4][5][6][7]. However, latest calculations based on the Gaussian expansion method suggested that the SO(10) symmetry is broken down to SO(3) instead of SO(4) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this is not straightforward since the complex Langevin method may suffer from the singular-drift problem due to the near-zero eigenvalues of the Dirac operator. The deformation technique [12] used successfully in studying the Euclidean version [13] is worth trying, though. We consider that the dominance of classical solutions at late times [26,27] supported by our results is important because it enables us to understand possible late-time behaviors of this model by solving classical equations of motion.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently the complex Langevin method (CLM) [4,5] has been attracting much attention as a promising approach to this problem [6][7][8][9][10][11][12]. In particular, it has been applied successfully to the Euclidean version of the 6D type IIB matrix model [13], and the spontaneous breaking of the rotational SO(6) symmetry to SO(3) suggested by the Gaussian expansion method [14] has been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Complex Langevin dynamics has been used successfully in various models in the recent past [13][14][15][16][17][18][19][20][21][22]. There have also been studies of supersymmetric matrix models based on complex Langevin dynamics [23][24][25]. In Ref.…”
mentioning
confidence: 99%